2023
DOI: 10.1371/journal.pbio.3002031
|View full text |Cite
|
Sign up to set email alerts
|

Individuals with problem gambling and obsessive-compulsive disorder learn through distinct reinforcement mechanisms

Abstract: Obsessive-compulsive disorder (OCD) and pathological gambling (PG) are accompanied by deficits in behavioural flexibility. In reinforcement learning, this inflexibility can reflect asymmetric learning from outcomes above and below expectations. In alternative frameworks, it reflects perseveration independent of learning. Here, we examine evidence for asymmetric reward-learning in OCD and PG by leveraging model-based functional magnetic resonance imaging (fMRI). Compared with healthy controls (HC), OCD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 101 publications
0
13
0
Order By: Relevance
“…Previous studies using probabilistic reversal learning tasks reported unchanged / increased learning rate for positive / negative RPEs in OCD patients [ 45 ] or increased / decreased learning rate for positive / negative RPEs in youth with OCD [ 46 ], and a recent study using a probabilistic instrumental learning task reported unchanged / decreased learning rate for positive / negative RPEs in OCD patients [ 47 ]. Reasons for these mixed results remain elusive, but our appetitive SR + aversive IR agent (large / small learning rate for positive / negative RPE in the SR-based system but the opposite pattern in the IR-based system) could potentially explain them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using probabilistic reversal learning tasks reported unchanged / increased learning rate for positive / negative RPEs in OCD patients [ 45 ] or increased / decreased learning rate for positive / negative RPEs in youth with OCD [ 46 ], and a recent study using a probabilistic instrumental learning task reported unchanged / decreased learning rate for positive / negative RPEs in OCD patients [ 47 ]. Reasons for these mixed results remain elusive, but our appetitive SR + aversive IR agent (large / small learning rate for positive / negative RPE in the SR-based system but the opposite pattern in the IR-based system) could potentially explain them.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for these mixed results remain elusive, but our appetitive SR + aversive IR agent (large / small learning rate for positive / negative RPE in the SR-based system but the opposite pattern in the IR-based system) could potentially explain them. Moreover, the recent study [ 47 ] has further shown that the decreased learning rate for negative RPEs in OCD was associated with attenuated representation of negative RPEs in the dorsomedial prefrontal cortex and the caudate. Given that the caudate (like dorsomedial striatum in rodents) has been implicated in model-based control (while putamen/dorsolateral striatum has been implicated in model-free control) [ 4 , 48 ], the attenuated representation of negative RPEs in the caudate in OCD can be consistent with our appetitive SR-based system having smaller learning rate for negative RPEs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study employing a probabilistic instrumental learning task with three conditions (reward, avoidance, neutral) found no overall differences in the proportion of correct choices between patients with GD and HCs in reward or avoidance trials. However, employing a computational model with two separate learning rates revealed that patients with GD exhibited relatively excessive sensitivity to positive prediction errors (PEs), but insensitivity to negative PEs ( Suzuki et al., 2023 ). These findings underscore the notion that GD might be linked to subtle and specific differences in learning rates, which might not always be easily discernible without employing sensitive experiments and computational modeling ( Hales et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this inverse relationship between reward prediction errors and fMRI signals in the dACC was notably diminished in OCD patients. Suzuki et al (2023) explored neural computations in RL among OCD patients using a modified two-armed bandit task, where decisions to seek rewards and avoid losses were randomly interleaved across trials. Their findings demonstrated that the RL model with asymmetric learning rates more accurately predicted behavior in rewardseeking contexts for both OCD patients and healthy controls, compared to the conventional RL and RL with perseverance models.…”
Section: Subsequent Comparisons Of the Parameter Estimates Between Pa...mentioning
confidence: 99%